Sensitivity analysis of a climate vulnerability index - a case study from Indian watershed development programmes - Raghavan Sathyan, Archana; Funk, Christoph; Aenis, Thomas; Winker, Peter; Breuer, Lutz; Justus Liebig University Giessen (My University, 2018)
Background: This paper presents a detailed analysis of a composite Climate Vulnerability Index (CVI) to examine and compare climate change vulnerability and its dimensions adaptive capacity, sensitivity and exposure. Thereby, we are mainly interested on climate change vulnerability at community-level watershed development programmes and how the different implementing agencies could help to address the problems associated with climate change in future planning and implementation.Method: The primary data used for this study was obtained from household surveys (n=215) in three watershed communities of Kerala, India. We use bootstrap sampling and a leave-one-out sensitivity analysis to compare the climate vulnerability of the three examined watersheds in detail. By introducing the bootstrapping method and sensitivity analysis into the research field of climate vulnerability, the paper describes significant differences in CVI values and the influencing indicators to the overall vulnerability at the watershed community level.Results The results show that there are significant differences in the exposure and sensitivity dimensions of vulnerability even if the overall CVI shows less variability and no significant differences among the three watersheds. The sensitivity analysis emphasizes that Livelihood Strategies and SSocial Network are the most influencing major components of vulnerability. This suggests that implementing agencies should focus on these two major components in order to improve the watershed development programmes. Conclusion The bootstrapping approach is transferable to evaluate the degree of influence of indicators on a composite index like the CVI. Moreover, it allows us to evaluate the potential effectiveness of various other climate change programmes where the evaluation is commonly done by field surveys. This thereby helps to increase the credibility in the examination of the impacts of climate change at different scales in order to find key areas for better policy planning.
Keywords: Bootstrapping; Climate change adaptation; Climate vulnerability assessment; Climate vulnerability index; Sensitivity analysis; ddc:630